Designing An Automatic Microcontroller-based Drying Machine of Coffee Beans - Derisma Derisma; Afdholli Putra; Dodon Yendri (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
This research was aimed to create an automatic microcontroller-based coffee beans drying machine without the support of sunlight to produce SNI-standardized coffee beans with small content of water or amounted to 12%. The designed machine consists of a tube-shaped container with 50 cm length and 11 cm radius, soil moisture sensor, DS18B20 temperature sensor, heater, motor DC, relay 2 channel and arduino uno microcontroller. The drying works when soil moisture sensor detects 12% of water content from big coffee beans. The drying process is done by applying heater to dry the coffee beans and the motor DC is used as the rotator of the container to evenly dry the coffee beans. The temperature of the drying container is around 51oC-55oC because the surface of coffee beans will be damaged if the temperature is above 55oC. When the water content of coffee beans is low or equal to 12%, the drying process is terminated. The drying process of heavy coffee beans (1kg) with 25.34% of initial water content takes 60 minutes with 11.74% of final water content as the result, While the drying process with the help of sunlight required approximately 310 minutes with 11.83% of final water content. It has been proved that the drying with machine was faster compared to the drying process through sunlight.